2018
DOI: 10.1001/jamaophthalmol.2018.3293
|View full text |Cite
|
Sign up to set email alerts
|

Association of Corticosteroid Use With Incidence of Central Serous Chorioretinopathy in South Korea

Abstract: on the incidence of central serous chorioretinopathy (CSC) in individuals who receive corticosteroids is scarce but clinically important because these agents are useful and widely used. OBJECTIVE To estimate the annual and 5-year incidence of CSC in South Korea in the overall population and in those who have used corticosteroid medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
4
10
0
Order By: Relevance
“…Recently, a population-based study in Korea reported an annual CSC incidence rate of 3.5 per 10,000 person-years (5.4 and 1.6 per 10,000 person-years in men and women, respectively). 13 In the present study, the incidence of CSC was 19.61 per 100,000 person-years (30.49 and 8.88 per 10,000 person-years in men and women, respectively). The lower incidence of CSC in our study may be the result of differences in the strict definition of CSC (i.e., use of optical coherence tomography examination for diagnosis) and exclusion criteria.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Recently, a population-based study in Korea reported an annual CSC incidence rate of 3.5 per 10,000 person-years (5.4 and 1.6 per 10,000 person-years in men and women, respectively). 13 In the present study, the incidence of CSC was 19.61 per 100,000 person-years (30.49 and 8.88 per 10,000 person-years in men and women, respectively). The lower incidence of CSC in our study may be the result of differences in the strict definition of CSC (i.e., use of optical coherence tomography examination for diagnosis) and exclusion criteria.…”
Section: Discussionsupporting
confidence: 45%
“…The annual incidence of CSC per 10,000 person-years is 2.1 in Taiwanese, 3.5 in Korean, and 1.0 in Caucasian populations. [12][13][14] Furthermore, polypoidal choroidal vasculopathy (or aneurysmal Type 1), a distinct subtype of exudative AMD, accounts for 20% to 55% of exudative AMD in Asian populations but only 8% to 13% in Caucasian populations. 15 Whether the subtype of exudative AMD is associated with the history of CSC is an important question, but at present, there is insufficient evidence to confirm this.…”
mentioning
confidence: 99%
“…These rare diseases were selected based on a previous review on OCT diagnosis [ 24 ]. According to the Orphan database, central serous chorioretinopathy [ 25 ], Stargardt disease [ 26 ], and retinitis pigmentosa [ 27 ] are considered as rare retinal diseases [ 28 ]. Because macular telangiectasia [ 29 ] and macular hole [ 30 ] also have very low prevalence, it is reasonable to consider them as relatively rare diseases.…”
Section: Methodsmentioning
confidence: 99%
“…However, in contrast to the other GCs-induced side effects, the route of GCs administration influences the risk of CSCR. The nasal, articular, oral and dermal routes favor CSCR [12][13][14][15][16][17][18][19][20][21] but not the high and sustained intraocular GCs [22,23]. This clinical observation led us to hypothesize that it is not the increase in ocular GCs levels but rather a consequence of systemic corticosteroids on ocular corticosteroids that may be the link between CSCR and corticosteroid therapy.…”
Section: Introductionmentioning
confidence: 99%